Internet addiction: When the positive emotions are not so positive. (May 2019) - Longstreet, Phil; Brooks, Stoney; Gonzalez, Ester S.
Abstract: Internet Addiction has emerged as a universal issue affecting a multitude of people. Internet addiction may be brought about by the simple fact of using coping in combination with internet technologies to escape from the negative emotions of daily live and promote more positive emotions. Drawing on this coping theory, this manuscript reports the results of a study designed to explore the relationships between internet addiction and positive/negative emotional states. Internet users were surveyed about their internet usage patterns and some basic emotions. These survey results were then analyzed using PLS. The results showed significant relationships between internet addiction and the emotional states. Specifically, internet addiction is found to concurrently increase the negative emotional states and decrease the positive emotional states. This is troubling as internet usage has been steadily increasing. The findings show that if the usage is from an Internet addict, the usage can decrease the positive and increase the negative emotional states. Highlights: Coping is the way many deal with personal issues but it may contribute to internet addiction. We model Internet Addiction as affecting both positive and negative emotion states. Increasing Internet Addiction will decrease happiness and life satisfaction. Increasing Internet Addiction will increase depression and loneliness.